A Theoretical Study on the Optical Spectroscopic Properties of Indigoids@B36 - Tugba Tugsuz (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2021)
Indigoids represent a family of environmentally friendly organic semiconductor materials. In this study, we aim to fine-tune the optoelectronic properties and semiconductor performance of indigoids by careful choice of the functional groups. We used Density Functional Theory (DFT) to predict the electron transport behavior of indigoids by calculating their electronic properties. The time-dependent DFT (TD-DFT) method was employed to explore the absorption spectra properties of indigo and indigoid molecules. To improve the performance of organic semiconductors, we modeled indigoids on borophene cluster. Using TD-DFT method, the absorption properties were predicted. The maximum absorption for the complex corresponding to the transition between Highest Occupied Molecular Orbital (HOMO) and Lowest Unoccupied Molecular Orbital (LUMO) showed a charge transfer transition as the electron density of the HOMO is located on the borophene and that of the LUMO on indigo and indigoids. The presence of charge transfer peaks of the absorption spectrum, the indigo and indigoids@B36 complexes were found as suitable for optoelectronic devices.